Impact of exposure to low levels of mercury on the health of dental workers - Jesus, Leda Freitas; Moreira, Fátima Ramos (Acta Scientiarum. Health Sciences, 2016)
This work evaluated the impact of exposure to mercury on the health of workers comparing dentists and dental assistants exposed to mercury by handling amalgam in a public dental clinic with a reference group which, in private offices, did not make use of the metal in their professional routine. Data collection included mercury levels in urine and air samples determined by cold vapor atomic absorption spectrometry, questionnaires and direct observation. The difference between urine and air samples in both groups was statistically significant while mercury levels in air and urine showed positive associations. Mercury concentration in urine correlated with gender, practice time, and age of workers. Half of those exposed had complaints compatible with mercury contamination. Among the exposed, the most common complaints were cognitive and neurocognitive symptoms. Correlations between symptoms and exposure time and also number of amalgam fillings placed per week were positive. Amalgam handling resulted in environmental and biological contamination by mercury.